Analysis of the Internal Structure and Psychometric Properties of the Entrapment Scale in Spanish Adolescents and Emerging Adults - Ana Huertes-del Arco; Eva Izquierdo-Sotorrío; Isabel Ramírez-Uclés; Miguel A. Carrasco; Francisco Pablo Holgado-Tello (European Journal of Investigation in Health, Psychology and Education, 2025)
The Entrapment Scale was developed to measure the feeling of being trapped by external situations or internal experiences (such as thoughts and emotions) without the possibility of escape. This perception, especially when combined with feelings of defeat, is central to integrated motivational–volitional (IMV) model of suicidal behavior. This study adapts the Entrapment Scale for Spanish adolescents and emerging adults, focusing on its internal structure, reliability, and criterion validity. We assessed 849 participants (48.1% male) aged 12 to 22 and compared three models: a correlated two-factor model, a second-order factor model, and a bifactor model. The bifactor model showed the best fit, indicating that a general entrapment factor influenced all items, while specific internal and external factors captured unique aspects. Importantly, distinguishing between internal and external entrapment can guide the development of more personalized and effective therapeutic strategies, as the relevance of each dimension may vary depending on the behaviors or symptoms present. This approach allows clinicians to target interventions more precisely to the individual’s needs. Theoretical and practical implications for understanding and addressing suicidal behavior are discussed.